Pensamento Computacional e a Ação Computacional por Ensino Remoto: Um relato de experiência de uso do AppInventor em meio a pandemia de COVID-19 - Farias, Eder Jacques; Carvalho, Windson Viana de; Matos, Maria Elisa Gomes de; Rodrigues, George; Castro, Jerry Macedo; Santos, Alysson Diniz dos (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na Educação, 2020)
Considering the relevance of Computational Thinking (CT) and the need to develop this competence in Computer Science (CS) students.This paper presents and evaluates a CT course, given remotely, to students in the first semester of the CS. The course aimed to learn CT using Computational Action. The applications were designed using Design Thinking and developed on the block programming platform, App Inventor. The results indicate that after the course the students showed a visible increase in knowledge about the CT and in the motivation to learn more about the subject.